2008
DOI: 10.1016/j.jiph.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic human papilloma virus and cervical pre-cancerous lesions in brothel-based sex workers in India

Abstract: A community-based cross-sectional study was conducted in brothel-based sex workers of West Bengal, Eastern India, to determine their oncogenic human papillomavirus (HPV) status and the presence of pre-cancerous lesions. A total of 229 sex workers from three districts of West Bengal participated in the study. All the study participants were interviewed with the aid of a pre-tested questionnaire to determine their sociodemographics, risk behaviour and risk perceptions after obtaining informed verbal consent. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Even in studies among sex workers, a population which is highly exposed to HPV, Kjaer et al and Sarkar et al observed a considerably decreasing trend in HPV prevalence with age in spite of continuous high levels of sexual activity. [17,18] This is probably due to development of acquired immunity to HPV infection following repeated exposure. But, in this study, it was found that the prevalence of HPV 16/18 to be almost constant across different age groups among the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in studies among sex workers, a population which is highly exposed to HPV, Kjaer et al and Sarkar et al observed a considerably decreasing trend in HPV prevalence with age in spite of continuous high levels of sexual activity. [17,18] This is probably due to development of acquired immunity to HPV infection following repeated exposure. But, in this study, it was found that the prevalence of HPV 16/18 to be almost constant across different age groups among the controls.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, frequent re- infection/reactivation due to multiple sex-partners, increased frequency of sex etc. might have helped in the development of immunity against HPV among sex workers in the study by Sarkar et al [18] which included young unmarried women. An in-depth cohort study from this region is required to understand this.…”
Section: Discussionmentioning
confidence: 99%
“…Also, both male and female sex workers may be at high risk of HPV infection due to multiple sexual partners and unprotected sexual activities, which can lead to the HPV transmission from person to person. (5)…”
Section: Introductionmentioning
confidence: 99%
“…Jia [37] 2015 China 309 Gomih-Alakija [38] 2014 Kenya 349 Aho [39] 2014 Guinea 223 Wang [40] 2013 China 288 Patel [41] 2013 Kenya 296 Marek [42] 2013 Hungary 34 Hoang [43] 2013 Vietnam 281 Ersan [11] 2013 Turkey 239 Yin [44] 2013 China 802 Keten [45] 2013 Turkey 137 Li [46] 2012 China 810 Huq [47] 2012 Bangladesh 809 Ghosh [48] 2012 India 45 Couture [49] 2012 Cambodia 220 Brown [50] 2012 Peru 199 Shikova [51] 2011 Bulgaria 106 Montano [52] 2011 Peru 87 Matsushita [53] 2011 Japan 196 Dal Pogetto [54] 2011 Brazil 102 Znazen [55] 2010 Tunisia 188 Smith [56] 2010 Madagascar 90 Luchters [57] 2010 Kenya 776 Rhee [58] 2010 South Korea 2308 Valle`s [59] 2009 Guatemala 297 Miyashita [60] 2009 Philippines 369 del Amo [61] 2009 Spain 549 Sultana [62] 2008 Bangladesh 293 Sarkar [63] 2008 India 229 Hernandez [64] 2008 Vietnam 282 Yun [65] 2008 South Korea 188 Gazi [66] 2008 Turkey 124 Didelot-Rousseau [67] 2006 Burkina Faso 360…”
Section: Study Characteristicsmentioning
confidence: 99%